PENINGKATAN KETERAMPILAN MOTORIK HALUS ANAK MELALUI KEGIATAN FINGER PAINTING TAMAN KANAK-KANAK AN NAJAH SEKAMPUNG LAMPUNG TIMUR - Sri Wahyuni, (UNISAN JURNAL, 2024)
This research aims to improve fine motor skills through finger painting activities in group B1 children at An Najah Sekampung Kindergarten, East Lampung. This research is collaborative classroom action research. The subjects of this research were children in the 5-6 year old group at An Najah Sekampung Kindergarten, totaling 15 children. The data collection method uses observation. The techniques used for data analysis are qualitative and quantitative descriptive. Based on the results of the discussion, it can be concluded that children's fine motor skills can be improved through finger painting activities. Improving fine motor skills is carried out by providing colorful porridge with colors that children like, so that children are interested in participating in finger painting activities, and repeating examples so that children can better understand and master finger painting activities. The average achievement of the number of children who had fine motor skills during pre-action was at the criteria of starting to develop (46.11%). After taking action in Cycle I to Cycle II there was an increase to 81.48%. Keywords : fine motor skills, finger painting activities, group B1 child